2002
DOI: 10.1002/1521-4141(200208)32:8<2264::aid-immu2264>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Receptor editing in CD45-deficient immature B cells

Abstract: B cell receptor signaling threshold regulates negative selection of autoreactive B cells and determines the mechanism of B cell tolerance. Using mice carrying immunoglobulin transgene specificfor MHC class I antigen Kk (3–83Tg mice), and IL‐7‐driven bone marrow (BM) culture system, we have previously shown that receptor editing is a major mechanism in B cell tolerance. To test the role of BCR signaling competence on the induction of tolerance‐mediated receptor editing, we crossed the 3–83Tg mice with mice defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Ϫ/Ϫ and CD19 Ϫ/Ϫ mice showed relatively mild defects in the transitional B cell compartment in the spleen (39,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ/Ϫ and CD19 Ϫ/Ϫ mice showed relatively mild defects in the transitional B cell compartment in the spleen (39,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, however, tonic signals have not been measured directly. In contrast, lack of CD45 has no effect on B cell development and positive selection (45).…”
Section: Establishment Of Appropriate Tonic Tyrosine Phosphorylation mentioning
confidence: 94%
“…3) (42). Modification of these signals by lack of CD19 or CD45 coreceptors or Btk have no effect on receptor editing stimulated by multivalent membrane-bound Ag (45,70,71). Analysis of affinity threshold revealed that receptor editing was efficiently stimulated by MHC Ags with affinities of Ͼ5 ϫ 10 4 M Ϫ1 (72).…”
Section: Receptor Editing In Negative Selectionmentioning
confidence: 99%